Case of mastocytemia and systemic mastocytosis in a dog ProCyte Dx and Sysmex XT-2000i scattergram findings, morphologic features, and c-kit somatic mutation analysis - Palić, Jelena (Veterinary clinical pathology, 2023)
© 2023 American Society for Veterinary Clinical Pathology.